Exploring social and cultural norms to promote ecologically sensitive residential garden design - Uren, H.; Dzidic, Peta; Bishop, Brian John (Elsevier, 2015)
Western Australia (WA) is experiencing severe water shortages associated with a drying climate. Suburban gardens in and around WA's capital city of Perth however, continue to be dominated by water dependent European style gardens featuring green lawns and introduced species. One area in metropolitan Perth going against this norm is the local government district of Fremantle. Residents within this city council have shown widespread adoption of native gardens: a seemingly obvious means of reducing water use and increasing local biodiversity. In an endeavour to understand the differences in garden design preferences, the aim of this research was to explore cultural and psychological drivers of native gardening within the city of Fremantle. Twelve in-depth, face-to-face semi-structured interviews were conducted with Fremantle homeowners. Participants had converted their garden from a traditional European design in favour of an aesthetic based on native species. Drivers such as knowledge, functionality, and social norms emerged, and interestingly resembled the same sorts of drivers previously identified as driving European style gardening practices in Australia. We account for the tension of same drivers yet different design due to differences in social and cultural values. Specifically, the dominant worldview in Fremantle is pro-environmental and this driver appears to shape the social context in which gardening decisions are made, making for a more accepting setting for residents to adopt alternative garden designs. Findings from this research are of value to water and environmental policy makers, urban local governments, and environmental educators.